Crack-resistant construction method for water-stabilized base based on basalt fiber mixture optimization
By adding basalt fibers and other additives to the mixture of water-stabilizing base layer, the formulation and construction process are optimized, and the problem of cracking is prone to occur in traditional water-stabilizing base layers is solved, which significantly improves crack resistance, extends service life and reduces maintenance costs.
Patent Information
- Application Number
- CN202411799757.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional highway water-stabilizing base layers are prone to crack problems during long-term use, resulting in reduced load-bearing capacity and increased moisture permeability, which in turn damages the structural integrity of the base and surface layers and increases maintenance costs and frequency.
By adding basalt fibers to the mixture and combining the use of other additives, the formulation and construction process of the water-stabilizing base layer are optimized to form a mesh structure to restrict the shrinkage and deformation of the base layer and improve the crack resistance of the base layer.
It significantly improves the crack resistance of the water-stabilized base layer, extends the service life of the highway, reduces maintenance costs, and ensures the stability and durability of the base layer.
Smart Images

Figure CN119824746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-stable base construction, and in particular to an anti-cracking construction method for a water-stable base based on optimization of a basalt fiber mixture. Background Art
[0002] Cement stabilized gravel base, referred to as "water-stable base", is a commonly used road base material. It has the advantages of high strength, good stability and good durability, and is widely used in highways, urban roads, airport runways and other projects. In modern highway construction, the water-stable base is an important part of the highway structure, and its performance directly affects the service life and driving safety of the highway. The water-stable base has the following performance characteristics: High strength: The cement stone formed after cement hydration has high strength and can withstand large loads. Good stability: The water-stable base has good stability and is not prone to deformation and settlement. Good durability: The water-stable base has good durability and can be used for a long time. Convenient construction: The water-stable base has a simple construction process and a fast construction speed.
[0003] However, traditional highway water-stable base layers often develop cracks during long-term use. These cracks not only reduce the load-bearing capacity of the highway, but also lead to water penetration, further damaging the structural integrity of the base and surface layers, and increasing maintenance costs and frequency. Summary of the invention
[0004] In order to overcome the defects in the prior art, the present invention provides a water-stable base anti-cracking construction method based on basalt fiber mixture optimization, by adding basalt fiber to the mixture, the crack resistance, stability and durability of the water-stable base are improved.
[0005] In order to achieve the above object, the present invention provides a water-stable base anti-cracking construction method based on basalt fiber mixture optimization, comprising:
[0006] Provide basalt fiber raw materials, water-stable crushed stone raw materials, cement, and fly ash;
[0007] Pre-wetting the basalt fiber raw material, and dispersing the pre-wetted basalt fiber raw material according to a designed ratio to form basalt fiber;
[0008] Weigh different weight portions of basalt fiber, water-stable crushed stone raw material, cement, fly ash and additives and mix and stir to obtain a mixture;
[0009] The mixture is spread on the surface of the road base, and after the spreading is completed, it is rolled to form a water-stable base;
[0010] Carry out health treatment on water-stable base;
[0011] Complete the anti-cracking construction of the water-stable base.
[0012] Preferably, when providing basalt fiber, water-stabilized crushed stone raw materials, cement and fly ash, basalt fiber raw materials whose length, diameter and tensile strength indicators meet the requirements of the specifications are selected, and water-stabilized crushed stone raw materials whose grading, crushing value and mud content indicators meet the design requirements are selected.
[0013] Preferably, the water-stable crushed stone raw materials include water-stable crushed stone, water, slag powder, and lime, and the additives include water reducers, antifreeze agents, impermeability agents, retarders, and anti-cracking agents. When weighing different weight portions of basalt fiber, water-stable crushed stone raw materials, cement, fly ash, and additives and mixing and stirring, the weight portions of each material weighed include:
[0014] 950-1000 parts of water-stabilized gravel;
[0015] 3-6 parts of basalt fiber;
[0016] Cement 100-150 parts;
[0017] Fly ash 50-100 parts;
[0018] 130-160 parts of water;
[0019] 30-50 parts of slag powder;
[0020] Water reducing agent 0.5-1.0 parts;
[0021] 10-20 parts lime
[0022] 1-3 parts antifreeze
[0023] 1-2 parts of anti-seepage agent;
[0024] Retarder 0.5-1.0 part;
[0025] 1-3 parts of anti-cracking agent.
[0026] Preferably, different weight portions of basalt fiber, water-stable crushed stone raw material, cement, fly ash and additives are mixed and stirred using an intermittent mixer, and the stirring time is controlled so that the basalt fiber is fully dispersed.
[0027] Preferably, before paving the mixture on the surface of the road base, the surface of the road base is cleaned to ensure that there is no debris or loose soil on the surface of the road base.
[0028] Preferably, when paving the mixture on the surface of the road base, the paving speed and thickness are controlled.
[0029] Preferably, when rolling after paving is completed, follow the principle of light first then heavy, slow first then fast, so as to ensure dense rolling without leakage or overpressure.
[0030] Preferably, when curing the water-stable base layer, a covering film and watering measures are adopted to keep the surface of the water-stable base layer moist, and the curing time is not less than 7 days.
[0031] Preferably, during the curing treatment of the water-stable base layer, the compaction, flatness and strength indicators of the water-stable base layer are regularly tested.
[0032] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0033] 1) By adding basalt fiber to the mixture and combining it with other additives, the crack resistance of the water-stable base of the highway is significantly improved. Basalt fiber has high tensile strength and elastic modulus. When the fibers in the mixture form a mesh structure, it can effectively restrain the shrinkage deformation of the base and reduce the generation and development of cracks. In addition, the addition of basalt fiber increases the toughness of the mixture, allowing the base to better absorb energy when subjected to external loads or temperature changes, thereby reducing cracks caused by stress concentration. This is particularly important during highway operation, because cracks not only affect driving comfort, but may also lead to water penetration, further damaging the structural integrity of the base and surface layers. Therefore, this method extends the service life of the highway and reduces maintenance costs by improving crack resistance.
[0034] 2) By specifying each step and parameter in the construction process in detail, the stability and reliability of the project quality are ensured: strict control of mixing time, mixer speed, and regular mixture inspection ensure that basalt fiber can be fully mixed with other materials, avoiding fiber agglomeration and uneven mixture problems; precise control of the selection of rollers, rolling speed, and number of passes ensures that the compaction of the base meets the design requirements, thereby improving the bearing capacity and durability of the base. The control of these details enables each step of the construction process to be effectively managed, reduces human errors, and improves construction efficiency. Ultimately, these measures work together to significantly improve the strength, stability, and durability of the highway water-stable base, provide solid support for the superstructure, and ensure the quality of the entire highway project. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1The present invention is a flow chart of the water-stable base cracking resistance construction method based on basalt fiber mixture optimization. DETAILED DESCRIPTION
[0037] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] See also Figure 1 As shown, the present invention provides a method for anti-cracking construction of a water-stable base based on optimization of basalt fiber mixture, comprising the following steps:
[0039] Provide basalt fiber raw materials, water-stable crushed stone raw materials, cement, and fly ash;
[0040] Pre-wetting the basalt fiber raw material, and dispersing the pre-wetted basalt fiber raw material according to a designed ratio to form basalt fiber;
[0041] Weigh different weight portions of basalt fiber, water-stable crushed stone raw material, cement, fly ash and additives and mix and stir to obtain a mixture;
[0042] The mixture is spread on the surface of the road base, and after the spreading is completed, it is rolled to form a water-stable base;
[0043] Carry out health treatment on water-stable base;
[0044] Complete the anti-cracking construction of the water-stable base.
[0045] Example 1
[0046] A method for anti-cracking construction of a water-stable base based on optimization of basalt fiber mixture, the method comprising the following steps:
[0047] Select high-quality basalt fiber raw materials, and ensure that their length, diameter, tensile strength and other indicators meet the specifications; prepare water-stable crushed stone raw materials, and ensure that their gradation, crushing value, mud content and other indicators meet the design requirements; prepare cement, fly ash and other cementitious materials to ensure their quality;
[0048] The basalt fiber raw material is pre-wetted to increase its bonding performance with the mixture, and the pre-wetted basalt fiber raw material is dispersed according to the designed proportion to form basalt fiber and ensure that it is evenly distributed in the mixture;
[0049] Weigh:
[0050] 950 parts by weight of water-stable crushed stone;
[0051] 3 parts by weight of basalt fiber;
[0052] 100 parts by weight of cement;
[0053] 50 parts by weight of fly ash;
[0054] Water 130 parts by weight;
[0055] 30 parts by weight of slag powder;
[0056] 0.5 parts by weight of water reducing agent;
[0057] 10 parts by weight of lime
[0058] Antifreeze agent 1 part by weight
[0059] 1 part by weight of an anti-seepage agent;
[0060] 0.5 parts by weight of retarder;
[0061] 1 part by weight of anti-cracking agent, and then ensure that the maximum dry density, optimum moisture content and other parameters of the mixture meet the design requirements;
[0062] Use an intermittent mixer to mix the mixture to ensure uniform mixing, and control the mixing time to ensure that the basalt fiber is fully dispersed;
[0063] Use closed transport vehicles to transport the mixture to the construction site, and pay attention to reducing the segregation and moisture loss of the mixture during transportation;
[0064] Clean the surface of the base to ensure there is no debris or loose soil, and use a paver to spread the mixture, controlling the spreading speed and thickness;
[0065] Use appropriate rollers for rolling, following the principle of light first then heavy, slow first then fast to ensure compaction without leaking or over-pressuring.
[0066] After the mixture is rolled, it should be cured immediately by covering with film, sprinkling water, etc. to keep the surface of the water-stable base moist, and the curing time should be no less than 7 days;
[0067] During the curing period, regularly check the compaction, flatness, strength and other indicators of the water-stabilizing base layer. If any problems are found, deal with them in a timely manner to ensure that the quality of the water-stabilizing base layer meets the requirements.
[0068] The water reducer is one or more of a polycarboxylic acid water reducer, a naphthalene-based water reducer, an aliphatic water reducer, and an aminosulfonic acid water reducer.
[0069] Among them, the raw material of basalt fiber is one of pyrophyllite, amygdalite and andesite.
[0070] Among them, the antifreeze agent is one or more of calcium chloride, sodium sulfate, ethylene glycol and urea.
[0071] Among them, the anti-seepage agent is one or more of a silane-based waterproofing agent, a polyurea waterproofing agent, a water-based polyurethane waterproofing agent, and an alkyl silicate waterproofing agent.
[0072] Wherein, the retarder is one or more of molasses, citric acid, phosphate, sodium gluconate and borax.
[0073] Among them, when using an intermittent mixer to mix the mixture, the specific construction conditions are as follows:
[0074] 1) The capacity of the mixer should be at least 500 liters to meet the needs of batch mixing;
[0075] 2) During the mixing process, the speed of the mixer should be precisely controlled at 35 revolutions per minute, and the mixing time should be strictly controlled at 4 minutes. This is the optimal mixing time determined based on laboratory tests, which can ensure that basalt fibers are evenly distributed with cementitious materials such as water-stabilized crushed stone, cement, and fly ash, while avoiding fiber agglomeration;
[0076] 3) During the mixing process, the operator should check the color and humidity of the mixture every 30 seconds to ensure that the color of the mixture is consistent, the humidity is moderate, and there are no obvious dry or wet lumps;
[0077] 4) After mixing is completed, 5 samples are immediately taken from different parts for laboratory testing, including the fluidity, compressive strength and fiber dispersion uniformity of the mixture.
[0078] Among them, when using a roller for rolling, the specific construction parameters are as follows:
[0079] The weight of a light roller should be 8 to 10 tons, and the initial compaction speed should be controlled at 1.8 kilometers per hour, for two passes. Subsequently, a heavy roller should be used, which should weigh 12 to 15 tons. The re-compacting speed can be increased to 2.2 kilometers per hour, for six passes. During the compaction process, the edges and corners should be compacted an additional 1 to 2 times to ensure that there is no leakage. The overlapping width of the roller wheel tracks should be precisely controlled at 40% of the wheel diameter to achieve uniform compaction effect.
[0080] Among them, when curing after the mixture is rolled, the following construction measures are specifically included:
[0081] 1) During the curing period, double-layer plastic film should be used to cover the soil to reduce water evaporation. When the temperature is above 20℃, the watering frequency should be adjusted to once every 2 hours. When the temperature is below 10℃, the watering frequency can be appropriately reduced.
[0082] 2) During the curing period, a cordon should be set up around the construction site and equipped with dedicated personnel to guard it to prevent unauthorized vehicles and personnel from entering.
[0083] 3) The curing time is at least 7 days. During this period, the integrity of the covering material and the moisture status of the base layer should be checked every 24 hours, and a curing log should be recorded.
[0084] Among them, when conducting quality inspection during health preservation, the specific inspection conditions and parameters are as follows:
[0085] 1) Use a compaction tester to test the compaction of the base layer. The test points should be randomly distributed, and the compaction of each test point should reach more than 98%;
[0086] 2) Use a flatness meter to check the flatness of the base layer to ensure that the deviation does not exceed 5mm;
[0087] 3) Strength testing is carried out by core sampling. The core sampling locations should cover the entire construction area. The number of cores should be no less than 6, and the unconfined compressive strength of each core sample should not be less than 90% of the design strength;
[0088] 4) For parts that fail the inspection, they should be marked immediately, the reasons should be analyzed, and measures should be taken to repair them within 24 hours. After the repair, they should be re-tested until all indicators meet the design requirements.
[0089] It should be noted that during the construction process, special treatment is given to the joints to ensure that the joints are smooth and tight. At the same time, appropriate materials and methods are used to improve the crack resistance of the joints. After the construction is completed, relevant departments are organized to conduct acceptance.
[0090] Example 2
[0091] A method for anti-cracking construction of a water-stable base based on optimization of basalt fiber mixture, the method comprising the following steps:
[0092] Select high-quality basalt fiber raw materials, and ensure that their length, diameter, tensile strength and other indicators meet the specifications; prepare water-stable crushed stone raw materials, and ensure that their gradation, crushing value, mud content and other indicators meet the design requirements; prepare cement, fly ash and other cementitious materials to ensure their quality;
[0093] The basalt fiber raw material is pre-wetted to increase its bonding performance with the mixture, and the pre-wetted basalt fiber raw material is dispersed according to the designed proportion to form basalt fiber and ensure that it is evenly distributed in the mixture;
[0094] Weigh:
[0095] 1000 parts by weight of water-stable crushed stone;
[0096] 6 parts by weight of basalt fiber;
[0097] 150 parts by weight of cement;
[0098] 100 parts by weight of fly ash;
[0099] Water 160 parts by weight;
[0100] 50 parts by weight of slag powder;
[0101] 1.0 parts by weight of water reducing agent;
[0102] 20 parts by weight of lime
[0103] Antifreeze agent 3 parts by weight
[0104] 2 parts by weight of anti-seepage agent;
[0105] 1.0 weight part of retarder;
[0106] 3 parts by weight of anti-cracking agent, and then ensure that the maximum dry density, optimal moisture content and other parameters of the mixture meet the design requirements;
[0107] Use an intermittent mixer to mix the mixture to ensure uniform mixing, and control the mixing time to ensure that the basalt fiber is fully dispersed;
[0108] Use closed transport vehicles to transport the mixture to the construction site, and pay attention to reducing the segregation and moisture loss of the mixture during transportation;
[0109] Clean the surface of the base to ensure there is no debris or loose soil, and use a paver to spread the mixture, controlling the spreading speed and thickness;
[0110] Use appropriate rollers for rolling, following the principle of light first then heavy, slow first then fast to ensure compaction without leaking or over-pressuring.
[0111] After the mixture is rolled, it should be cured immediately by covering with film, sprinkling water, etc. to keep the surface of the water-stable base moist, and the curing time should be no less than 7 days;
[0112] During the curing period, regularly check the compaction, flatness, strength and other indicators of the water-stabilizing base layer. If any problems are found, deal with them in a timely manner to ensure that the quality of the water-stabilizing base layer meets the requirements.
[0113] The water reducer is one or more of a polycarboxylic acid water reducer, a naphthalene-based water reducer, an aliphatic water reducer, and an aminosulfonic acid water reducer.
[0114] Among them, the raw material of basalt fiber is one of pyrophyllite, amygdalite and andesite.
[0115] Among them, the antifreeze agent is one or more of calcium chloride, sodium sulfate, ethylene glycol and urea.
[0116] Among them, the anti-seepage agent is one or more of a silane-based waterproofing agent, a polyurea waterproofing agent, a water-based polyurethane waterproofing agent, and an alkyl silicate waterproofing agent.
[0117] Wherein, the retarder is one or more of molasses, citric acid, phosphate, sodium gluconate and borax.
[0118] Among them, when using an intermittent mixer to mix the mixture, the specific construction conditions are as follows:
[0119] 1) The capacity of the mixer should be at least 500 liters to meet the needs of batch mixing;
[0120] 2) During the mixing process, the speed of the mixer should be precisely controlled at 35 revolutions per minute, and the mixing time should be strictly controlled at 4 minutes. This is the optimal mixing time determined based on laboratory tests, which can ensure that basalt fibers are evenly distributed with cementitious materials such as water-stabilized crushed stone, cement, and fly ash, while avoiding fiber agglomeration;
[0121] 3) During the mixing process, the operator should check the color and humidity of the mixture every 30 seconds to ensure that the color of the mixture is consistent, the humidity is moderate, and there are no obvious dry or wet lumps;
[0122] 4) After mixing is completed, 5 samples are immediately taken from different parts for laboratory testing, including the fluidity, compressive strength and fiber dispersion uniformity of the mixture.
[0123] Among them, when using a roller for rolling, the specific construction parameters are as follows:
[0124] The weight of a light roller should be 8 to 10 tons, and the initial compaction speed should be controlled at 1.8 kilometers per hour, for two passes. Subsequently, a heavy roller should be used, which should weigh 12 to 15 tons. The re-compacting speed can be increased to 2.2 kilometers per hour, for six passes. During the compaction process, the edges and corners should be compacted an additional 1 to 2 times to ensure that there is no leakage. The overlapping width of the roller wheel tracks should be precisely controlled at 40% of the wheel diameter to achieve uniform compaction effect.
[0125] Among them, when curing after the mixture is rolled, the following construction measures are specifically included:
[0126] 1) During the curing period, double-layer plastic film should be used to cover the soil to reduce water evaporation. When the temperature is above 20℃, the watering frequency should be adjusted to once every 2 hours. When the temperature is below 10℃, the watering frequency can be appropriately reduced.
[0127] 2) During the curing period, a cordon should be set up around the construction site and equipped with dedicated personnel to guard it to prevent unauthorized vehicles and personnel from entering.
[0128] 3) The curing time is at least 7 days. During this period, the integrity of the covering material and the moisture status of the base layer should be checked every 24 hours, and a curing log should be recorded.
[0129] Among them, when conducting quality inspection during health preservation, the specific inspection conditions and parameters are as follows:
[0130] 1) Use a compaction tester to test the compaction of the base layer. The test points should be randomly distributed, and the compaction of each test point should reach more than 98%;
[0131] 2) Use a flatness meter to check the flatness of the base layer to ensure that the deviation does not exceed 5mm;
[0132] 3) Strength testing is carried out by core sampling. The core sampling locations should cover the entire construction area. The number of cores should be no less than 6, and the unconfined compressive strength of each core sample should not be less than 90% of the design strength;
[0133] 4) For parts that fail the inspection, they should be marked immediately, the reasons should be analyzed, and measures should be taken to repair them within 24 hours. After the repair, they should be re-tested until all indicators meet the design requirements.
[0134] It should be noted that during the construction process, special treatment is given to the joints to ensure that the joints are smooth and tight. At the same time, appropriate materials and methods are used to improve the crack resistance of the joints. After the construction is completed, relevant departments are organized to conduct acceptance.
[0135] Example 3
[0136] A method for anti-cracking construction of a water-stable base based on optimization of basalt fiber mixture, the method comprising the following steps:
[0137] Select high-quality basalt fiber raw materials, and ensure that their length, diameter, tensile strength and other indicators meet the specifications; prepare water-stable crushed stone raw materials, and ensure that their gradation, crushing value, mud content and other indicators meet the design requirements; prepare cement, fly ash and other cementitious materials to ensure their quality;
[0138] The basalt fiber raw material is pre-wetted to increase its bonding performance with the mixture, and the pre-wetted basalt fiber raw material is dispersed according to the designed proportion to form basalt fiber and ensure that it is evenly distributed in the mixture;
[0139] Weigh:
[0140] 980 parts by weight of water-stable crushed stone;
[0141] 5 parts by weight of basalt fiber;
[0142] 130 parts by weight of cement;
[0143] 60 parts by weight of fly ash;
[0144] Water 150 parts by weight;
[0145] 40 parts by weight of slag powder;
[0146] 0.8 parts by weight of water reducing agent;
[0147] 15 parts by weight of lime
[0148] 2 parts by weight of antifreeze agent
[0149] 1.5 parts by weight of anti-seepage agent;
[0150] Retarder 0.7 parts by weight;
[0151] 12 parts by weight of anti-cracking agent, and then ensure that the maximum dry density, optimal moisture content and other parameters of the mixture meet the design requirements;
[0152] Use an intermittent mixer to mix the mixture to ensure uniform mixing, and control the mixing time to ensure that the basalt fiber is fully dispersed;
[0153] Use closed transport vehicles to transport the mixture to the construction site, and pay attention to reducing the segregation and moisture loss of the mixture during transportation;
[0154] Clean the surface of the base to ensure there is no debris or loose soil, and use a paver to spread the mixture, controlling the spreading speed and thickness;
[0155] Use appropriate rollers for rolling, following the principle of light first then heavy, slow first then fast to ensure compaction without leaking or over-pressuring.
[0156] After the mixture is rolled, it should be cured immediately by covering with film, sprinkling water, etc. to keep the surface of the water-stable base moist, and the curing time should be no less than 7 days;
[0157] During the curing period, regularly check the compaction, flatness, strength and other indicators of the water-stabilizing base layer. If any problems are found, deal with them in a timely manner to ensure that the quality of the water-stabilizing base layer meets the requirements.
[0158] The water reducer is one or more of a polycarboxylic acid water reducer, a naphthalene-based water reducer, an aliphatic water reducer, and an aminosulfonic acid water reducer.
[0159] Among them, the raw material of basalt fiber is one of pyrophyllite, amygdalite and andesite.
[0160] Among them, the antifreeze agent is one or more of calcium chloride, sodium sulfate, ethylene glycol and urea.
[0161] Among them, the anti-seepage agent is one or more of a silane-based waterproofing agent, a polyurea waterproofing agent, a water-based polyurethane waterproofing agent, and an alkyl silicate waterproofing agent.
[0162] Wherein, the retarder is one or more of molasses, citric acid, phosphate, sodium gluconate and borax.
[0163] Among them, when using an intermittent mixer to mix the mixture, the specific construction conditions are as follows:
[0164] 1) The capacity of the mixer should be at least 500 liters to meet the needs of batch mixing;
[0165] 2) During the mixing process, the speed of the mixer should be precisely controlled at 35 revolutions per minute, and the mixing time should be strictly controlled at 4 minutes. This is the optimal mixing time determined based on laboratory tests, which can ensure that basalt fibers are evenly distributed with cementitious materials such as water-stabilized crushed stone, cement, and fly ash, while avoiding fiber agglomeration;
[0166] 3) During the mixing process, the operator should check the color and humidity of the mixture every 30 seconds to ensure that the color of the mixture is consistent, the humidity is moderate, and there are no obvious dry or wet lumps;
[0167] 4) After mixing is completed, 5 samples are immediately taken from different parts for laboratory testing, including the fluidity, compressive strength and fiber dispersion uniformity of the mixture.
[0168] Among them, when using a roller for rolling, the specific construction parameters are as follows:
[0169] The weight of a light roller should be 8 to 10 tons, and the initial compaction speed should be controlled at 1.8 kilometers per hour, for two passes. Subsequently, a heavy roller should be used, which should weigh 12 to 15 tons. The re-compacting speed can be increased to 2.2 kilometers per hour, for six passes. During the compaction process, the edges and corners should be compacted an additional 1 to 2 times to ensure that there is no leakage. The overlapping width of the roller wheel tracks should be precisely controlled at 40% of the wheel diameter to achieve uniform compaction effect.
[0170] Among them, when curing after the mixture is rolled, the following construction measures are specifically included:
[0171] 1) During the curing period, double-layer plastic film should be used to cover the soil to reduce water evaporation. When the temperature is above 20℃, the watering frequency should be adjusted to once every 2 hours. When the temperature is below 10℃, the watering frequency can be appropriately reduced.
[0172] 2) During the curing period, a cordon should be set up around the construction site and equipped with dedicated personnel to guard it to prevent unauthorized vehicles and personnel from entering.
[0173] 3) The curing time is at least 7 days. During this period, the integrity of the covering material and the moisture status of the base layer should be checked every 24 hours, and a curing log should be recorded.
[0174] Among them, when conducting quality inspection during health preservation, the specific inspection conditions and parameters are as follows:
[0175] 1) Use a compaction tester to test the compaction of the base layer. The test points should be randomly distributed, and the compaction of each test point should reach more than 98%;
[0176] 2) Use a flatness meter to check the flatness of the base layer to ensure that the deviation does not exceed 5mm;
[0177] 3) Strength testing is carried out by core sampling. The core sampling locations should cover the entire construction area. The number of cores should be no less than 6, and the unconfined compressive strength of each core sample should not be less than 90% of the design strength;
[0178] 4) For parts that fail the inspection, they should be marked immediately, the reasons should be analyzed, and measures should be taken to repair them within 24 hours. After the repair, they should be re-tested until all indicators meet the design requirements.
[0179] It should be noted that during the construction process, special treatment is given to the joints to ensure that the joints are smooth and tight. At the same time, appropriate materials and methods are used to improve the crack resistance of the joints. After the construction is completed, relevant departments are organized to conduct acceptance.
[0180] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
Claims
1. A method for anti-cracking construction of a water-stable base based on optimization of basalt fiber mixture, characterized in that: The following steps are involved: Provide basalt fiber raw materials, water-stable crushed stone raw materials, cement, and fly ash; Pre-wetting the basalt fiber raw material, and dispersing the pre-wetted basalt fiber raw material according to a designed ratio to form basalt fiber; Weigh different weight portions of basalt fiber, water-stable crushed stone raw material, cement, fly ash and additives and mix and stir to obtain a mixture; The mixture is spread on the surface of the road base, and after the spreading is completed, it is rolled to form a water-stable base; Carry out health treatment on water-stable base; Complete the anti-cracking construction of the water-stable base.
2. The anti-cracking construction method of water-stable base based on basalt fiber mixture optimization according to claim 1 is characterized in that: When providing basalt fiber raw materials, water-stabilized crushed stone raw materials, cement and fly ash, select basalt fiber raw materials whose length, diameter and tensile strength indicators meet the requirements of the specifications, and select water-stabilized crushed stone raw materials whose grading, crushing value and mud content indicators meet the design requirements.
3. The anti-cracking construction method of water-stable base based on basalt fiber mixture optimization according to claim 1 is characterized in that: The water-stabilized crushed stone raw materials include water-stabilized crushed stone, water, slag powder, and lime. The additives include water reducers, antifreeze agents, impermeability agents, retarders, and anti-cracking agents. When weighing different weight portions of basalt fiber, water-stabilized crushed stone raw materials, cement, fly ash, and additives and mixing and stirring, the weight portions of each material weighed include: 950-1000 parts of water-stabilized gravel; 3-6 parts of basalt fiber; Cement 100-150 parts; Fly ash 50-100 parts; 130-160 parts of water; 30-50 parts of slag powder; Water reducing agent 0.5-1.0 parts; 10-20 parts lime 1-3 parts antifreeze 1-2 parts of anti-seepage agent; Retarder 0.5-1.0 part; 1-3 parts of anti-cracking agent.
4. The anti-cracking construction method for water-stable base based on basalt fiber mixture optimization as claimed in claim 1, wherein different weight portions of basalt fiber, water-stable crushed stone raw materials, cement, fly ash and additives are mixed and stirred using an intermittent mixer, and the stirring time is controlled to allow the basalt fiber to be fully dispersed.
5. According to the anti-cracking construction method of water-stable base based on basalt fiber mixture optimization as claimed in claim 1, before paving the mixture on the surface of the road base, the surface of the road base is cleaned to ensure that there is no debris or loose soil on the surface of the road base.
6. The anti-cracking construction method for water-stable base based on optimization of basalt fiber mixture as claimed in claim 1, wherein when paving the mixture on the surface of the road base, the paving speed and thickness are controlled.
7. The anti-cracking construction method for water-stable base based on basalt fiber mixture optimization as described in claim 1 follows the principle of light first then heavy, slow first then fast when rolling after paving is completed, so as to ensure compaction without leakage or overpressure.
8. According to the anti-cracking construction method of the water-stable base based on basalt fiber mixture optimization as described in claim 1, when the water-stable base is cured, a covering film and watering measures are adopted to keep the surface of the water-stable base moist, and the curing time is not less than 7 days.
9. The anti-cracking construction method of the water-stable base based on basalt fiber mixture optimization as claimed in claim 1, during the curing treatment of the water-stable base, the compaction, flatness and strength indicators of the water-stable base are regularly tested.
Citation Information
Patent Citations
Basalt fiber reinforced cement based material and preparation method therefor
CN105541209A
High-strength anti-cracking regenerated cement stabilized macadam material and preparation method thereof
CN108503301A
Construction process for cement stabilized macadam pavement
CN110331633A
Fiber-reinforced cement fly ash stabilized full-recycled brick-concrete aggregate pavement base material and preparation method thereof
CN110981329A
Road pavement quick repairing method
CN111005287A